Jaringan Komunikasi Pelaku Inovasi Agribisnis Kolam Ikan Air Deras di Kecamatan Caringin Kabupaten Bogor - Imsar Gunawan; Ninuk Purnaningsih; Basita Ginting (Jurnal Komunikasi Pembangunan, 2017)
Running water fish culture is one of the techniques in freshwater fish cultivation. This activity forms an agribusiness system and interactions from the individuals involved. These interactions form a communication network. This study aimed to provide a description of running water fish culture innovation, analyze the interpersonal communication networks in running water fish culture agribusiness, factors that influence the interpersonal communication networks, and analyze the factors that influence business sustainability. This research which used the census method was conducted in Caringin Subdistrict Bogor Regency. Survey results show that the communication network formed was of scattered personal networks. The outdegree centrality and indegree centrality values obtained were categorized as medium respectively. The closeness centrality value is also in the medium category. Whereas the betweenness centrality value for running water fish agribusiness participants is known to be the highest. Those individuals with high betweenness centrality values possess the ability to organize communication in their networks.